Plenjenje, normativne omejitve in neoliberalizem - Kanduč, Zoran (Revija za kriminalistiko in kriminologijo, 2020)
The aim of this paper is to highlight the role of plundering in lawful and incriminated forms of acquring incomes and in generating social-economic inequalities. In the introduction, the utter importance of the lifestyle based upon consumption (and consequently upon money being its necessary condition) in the neoliberal culture is dealt with. In the second section, acquisitive crimes are interpreted as a specific form of exchange representing a legally unnacceptable deviation from the equivalent contractual relationships. The third section is occupied with morally controversial, unearned, and undeserved ways of acquring goods in interpersonal relations otherwise founded upon the voluntary agreement of their participants. The final indicates briefly some reasons for preservation and even increasing private wealth.
Keywords: acquisitive crimes; bogastvo; inequalities; neenakosti; neoliberalism; neoliberalizem; plenjenje; plunder; premoženjska kriminaliteta; wealth